BMP- specific SMADs function as novel repressors of PDGFA and modulate its expression in ovarian granulosa cells and tumors - Tripurani, Swamy K. (2012)
Platelet-derived growth factor alpha (PDGFA) is frequently upregulated in various cancers and thought to function as a key player in the development and progression of tumor growth by regulating aspects of cell proliferation, angiogenesis, and metastasis. However, the mechanism by which it is upregulated is not fully understood. Previously, we demonstrated that conditional deletion of two transcription factors that signal for the bone morphogenetic proteins (Smad1 and Smad5) in ovarian granulosa cells causes metastatic granulosa cell tumors in female mice and phenocopies human juvenile granulosa cell tumors (JGCTs). Smad1/5 double conditional knockout tumors, as well as human JGCTs, are highly vascularized, hemorrhagic, and mitotically active. Expression analysis of these tumors and their metastases revealed a significant upregulation of key proliferation and pro-angiogenic factors such as Pdgfa, Pdgfb, and Vegf. We examined whether these genes were direct targets of SMAD1 and SMAD5. Knockdown of SMAD1 and SMAD5 in mouse primary granulosa cells and a human granulosa cell tumor-derived cell line (COV434) resulted in upregulation of PDGFA, but not PDGFB nor VEGF. We identified several putative SMAD1/5 binding sites in the PDGFA promoter, and chromatin immunoprecipitation and reporter assays demonstrated that SMAD1/5 interact with the PDGFA promoter to regulate its activity. Further, SMAD1/5 antagonize the activity of the transcription factor Sp1, a well-known positive regulator of PDGFA, by inhibiting its occupancy at a key regulatory site on the proximal PDGFA promoter. Collectively, our studies establish that loss of SMAD1/5 leads to upregulation of PDGFA in ovarian granulosa cells, and that a novel regulatory interaction exists between the BR-SMADs and Sp1 in controlling PDGFA expression during granulosa cell tumorigenesis.